-v+5+(6*v)=1+(5*v)+3

Simple and best practice solution for -v+5+(6*v)=1+(5*v)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -v+5+(6*v)=1+(5*v)+3 equation:


Simplifying
-1v + 5 + (6v) = 1 + (5v) + 3

Reorder the terms:
5 + -1v + (6v) = 1 + (5v) + 3

Combine like terms: -1v + (6v) = 5v
5 + 5v = 1 + (5v) + 3

Reorder the terms:
5 + 5v = 1 + 3 + (5v)

Combine like terms: 1 + 3 = 4
5 + 5v = 4 + (5v)

Add '-5v' to each side of the equation.
5 + 5v + -5v = 4 + (5v) + -5v

Combine like terms: 5v + -5v = 0
5 + 0 = 4 + (5v) + -5v
5 = 4 + (5v) + -5v

Combine like terms: (5v) + -5v = 0
5 = 4 + 0
5 = 4

Solving
5 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x-6x=-7x+6 | | 4a^2-16a+74=4 | | -40-2x=-5x+17 | | 2(3x)=3(x+2) | | -5=2g-9 | | 9y-43=5(y-7) | | 8.5(x+7.8)=90.23 | | a+12=65 | | 7x+y(0)=29 | | 3w^2+20w=7 | | 3(w-3)-9=-4(-5w+6)-7w | | 11.23(75.34-3x)=120.34 | | .5+3/5= | | 16.8a-v=6v | | 15.67-23.56=34.18x | | g=100-4t | | 0.25n-1.5=0.25n-1.5 | | -7(4x-7)=-80 | | P^2-20p+84=9 | | 111.78=67.8(2.7-4x) | | 4v-12-10=-5(v+9)-(v-6) | | 48+4x=-6+30-20x | | -11.0(x+3.33)=12.7 | | 3.7x+8=1.7x+9 | | 7x+1=-4-5 | | 7-6x=1-5x | | 4x^2+3xy-y^2=1 | | 33.8=7.6-2.06x | | 5b-4b=4b-2 | | 3t^2+22t+32=0 | | -17x-20-8x-2=128 | | 4(6-b)=12 |

Equations solver categories